Legibility of urban highway traffic signs using new retroreflective materials - Bullough, John D.; Skinner, Nicholas P.; O’Rourke, Conan P. (Transport, 2010)
Unlighted highway signs, which use newly developed retroreflective materials, were installed along the major expressway in an urban area by the local department of transportation. Photometric measurements of the signs were used to assess their legibility applying the relative visual performance model, in comparison to lighted signs, con‐ forming to recommended illumination practices. The calculated visibility of the measured unlighted signs was similar to that of the signs equipped with exterior sign illumination. The practical significance and limitations of the relative visual performance approach are discussed.First published online: 10 Feb 2011